Where do we know about it from? Lithuanian resistance and soviet terror in the literature of sixth-ninth decade - Daniel, Aleksandr (Genocidas ir rezistencija, 2008)
There is no reflection in the Russian mind about the deportation operations in the Baltic states. In the consciousness of the Russian masses, if it exists and records such events at all, the deportations were intertwined with other forms of repression – arrests, trials, sovietisation, collective farms and the mass suppression of partisan resistance. It was the partisan resistance of the Lithuanians that mainly struck the imagination of people who had already become unaccustomed to similar forms of armed resistance. The image of Lithuania as a partisan republic, which had suffered particularly brutal repressions, was formed in Russia.(?) This image was based on a variety of sources.
Keywords: Russia; Lithuania; terror; partisans; memory